A self-similar solution for the water hammer equation used in an infinite long pipeline. (August 2021) - Pistiner, Arieh
Abstract: The present study uses the self-similar approach, developed by Pistiner (2020), for solving the water hammer equation during the process of valve closure in infinite long pipeline. The obtained solution shows that the transient flow in the pipeline is characterized by three zones: the "near zone" located near the closing valve and is characterized by a positive flow; the "far zone" in the pipeline lying at an infinite distance from the valve where the flow is also positive and the "intermediate backflow zone", which is lying among the above-mentioned zones and is characterized by reverse flow. The results obtained in this study may be useful to give some insights into the understanding of transient flow process in pipes as well as provide approximate estimation for transient waves in pipes and finally, the applicability of the model to predict head distribution in the pipeline has been shown.